Value paradigm as a methodological basis for business valuation (Economics and region, 2023)
The aim of the study is to substantiate the procedure and expediency of using a number of methods based on the concept of value management when valuing a business in modern realities. It is proved that in the modern world, business valuation technologies have become a tool for building a highly efficient management system aimed at increasing the value of an enterprise, maximizing its profitability, and increasing its investment attractiveness. It is substantiated that the concept of value is rightly defined as the basic paradigm of business development. Based on a comparative characterization of modern approaches to business valuation from the perspective of decision-making on integration processes, the author proves that most of the methods are impossible or rather difficult to use for valuation of business in Ukraine due to the lack of a developed market for the purchase and sale of enterprises, objective information about their activities, and underdevelopment of the stock market. At the same time, it has been established that a number of world-class economists in their studies prove that the value of an enterprise depends on its ability to generate profit. Therefore, the study considers the procedure and features of applying the concept of economic profit EVA (Economic Value Added) in the valuation of business. The article characterizes and presents a schematic model of application of the DuRont methodology in the process of business valuation based on determining the level of efficiency of resource use. The author proves the necessity of business valuation, including the use of the outlined methodological approaches, since in the context of economic instability the market value is the main indicator that will allow making more informed decisions on maintaining the effective functioning of a business entity by owners, managers and investors.
Keywords: business valuation; value paradigm; concept of economic profit EVA (Economic Value Added); DuРont model; management